Osteoblast Extracellular Ca(2+)-Sensing Receptor Regulates Bone Development, Mineralization and Turnover - Dvorak-Ewell, Melita M. (2011)
The extracellular Ca(2+)-sensing receptor (CaR), a G protein-coupled receptor responsible for maintenance of calcium homeostasis, is implicated in regulation of skeletal metabolism. To discern the role of the osteoblast CaR in regulation of bone development and remodeling, we generated mice in which the CaR is excised in a broad population of osteoblasts expressing the 3.6 kb a(1)(I) collagen promoter. Conditional knockouts had abnormal skeletal histology at birth and developed progressively reduced mineralization secondary to retarded osteoblast differentiation, evident by significantly reduced numbers of osteoblasts and decreased expression of collagen I, osteocalcin and sclerostin mRNAs. Elevated expression of ankylosis protein, ectonucleotide pyrophosphatase/phosphodiesterase 1, and osteopontin mRNAs in the conditional knockout indicate altered regulation of genes important in mineralization. Knockout of the osteoblast CaR also resulted in increased expression of the receptor activator of nuclear factor kappa B ligand (RANK-L), the major stimulator of osteoclast differentiation and function, consistent with elevated osteoclast numbers in vivo. Osteoblasts from the conditional knockouts exhibited delayed differentiation, reduced mineralizing capacity, altered expression of regulators of mineralization and increased ability to promote osteoclastogenesis in co-culture experiments. We conclude that CaR signaling in a broad population of osteoblasts is essential for bone development and remodeling and plays an important role in the regulation of differentiation and expression of regulators of bone resorption and mineralization.